Pseudogap from ARPES experiment: three gaps in cuprates and topological superconductivity (Review Article) - Kordyuk, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
A term first coined by Mott back in 1968 a “pseudogap” is the depletion of the electronic density of states at the Fermi level, and pseudogaps have been observed in many systems. However, since the discovery of the high-temperature superconductors (HTSC) in 1986, the central role attributed to the pseudogap in these systems has meant that by many researchers now associate the term pseudogap exclusively with the HTSC phenomenon. Recently, the problem has got a lot of new attention with the rediscovery of two distinct energy scales (“two-gap scenario”) and charge density waves patterns in the cuprates. Despite many excellent reviews on the pseudogap phenomenon in HTSC, published from its very discovery up to now, the mechanism of the pseudogap and its relation to superconductivity are still open questions. The present review represents a contribution dealing with the pseudogap, focusing on results from angle resolved photoemission spectroscopy (ARPES) and ends up with the conclusion that the pseudogap in cuprates is a complex phenomenon which includes at least three different “intertwined” orders: spin and charge density waves and preformed pairs, which appears in different parts of the phase diagram. The density waves in cuprates are competing to superconductivity for the electronic states but, on the other hand, should drive the electronic structure to vicinity of Lifshitz transition, that could be a key similarity between the superconducting cuprates and iron-based superconductors. One may also note that since the pseudogap in cuprates has multiple origins there is no need to recoin the term suggested by Mott.